2012
DOI: 10.4103/2319-4170.104409
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learnt after the Introduction of the Seven Valent‑Pneumococcal Conjugate Vaccine Toward Broader Spectrum Conjugate Vaccines

Abstract: The 7-valent pneumococcal conjugate vaccine (PCV7) is currently being introduced in the vaccine schedule of over 90 countries around the world. After the introduction of the PCV7 vaccine in the United States, a reduction of more than 90% of invasive pneumococcal disease (IPD) was reported in vaccinated children under the age of 5 years. Similar findings were reported from other countries. A reduction in community-acquired pneumonia (CAP) of >40% has also been reported. In children under the age of 5 years, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
8
0
2
Order By: Relevance
“…Its effectiveness in preventing invasive pneumococcal disease (IPD) in infants and community-acquired pneumonia (CAP) has been clearly observed. However, it has been shown that the vaccine exerts a selective pressure on the serotypes not included in the vaccine [13]. This phenomenon of serotype replacement created a necessity for the development of new-generation recombinant protein vaccines, especially based on virulent factors conserved between strains [14].…”
Section: Introductionmentioning
confidence: 99%
“…Its effectiveness in preventing invasive pneumococcal disease (IPD) in infants and community-acquired pneumonia (CAP) has been clearly observed. However, it has been shown that the vaccine exerts a selective pressure on the serotypes not included in the vaccine [13]. This phenomenon of serotype replacement created a necessity for the development of new-generation recombinant protein vaccines, especially based on virulent factors conserved between strains [14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an outbreak of penicillin-resistant S. pneumoniae in Spain in 2011 was rapidly contained in 2012 owing to the introduction of the 7-valent pneumococcal conjugate vaccine (Fig. 7B) [22]. Finally, the significant reduction in the prevalence of MRSA in the UK in 2011 clearly matches the efforts in this country to improve surveillance and to combat MRSA bacteraemia (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The eff ectiveness of the new seven-valent pneumococcal conjugate vaccine in reducing disease burden and consequent unintended selection for the rise of serotypes that are not covered by the vaccine shows the importance of vaccination and continuous monitoring of target organisms. 380 Vaccines directed against organisms for which antibiotic resistance is especially challenging is a strategy that could have great clinical eff ect. Recent eff orts to develop vaccines for important drug resistant pathogens such as MRSA 381 and M tuberculosis 343,382 are promising, but have yet to generate viable candidates for late stage clinical trials.…”
Section: The Lancet Infectious Diseases Commissionmentioning
confidence: 99%